2008
DOI: 10.1111/j.1741-6248.2008.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Planning in Family Business: A Powerful Developmental Tool for the Next Generation

Abstract: This article addresses the issue of training next‐generation family members once they have joined the management team in their family firm. The qualitative analysis of strategic planning processes of 18 Italian family firms shows that involving next‐generation family members in the planning process benefits their developmental process. The findings indicate that this involvement provides the next generation with crucial tacit business knowledge and skills, facilitating interpersonal work relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 44 publications
(76 reference statements)
0
64
0
5
Order By: Relevance
“…One way to control and still provide space for creative innovation goes back to the 'stage-gate model' by Cooper (1990) that allows managers to innovate freely and only be controlled when switching to new 'gates'. To guide Autonomy, we follow the recommendations of prior family business research (Lane et al 2006) that suggest to guide Autonomy in family firms through explicit, written guidelines (Mazzola et al 2008). In addition, our findings indicate that adherence to family-related, often non-financial goals can lead to an unhealthy level of Risk-Taking.…”
Section: Resultsmentioning
confidence: 99%
“…One way to control and still provide space for creative innovation goes back to the 'stage-gate model' by Cooper (1990) that allows managers to innovate freely and only be controlled when switching to new 'gates'. To guide Autonomy, we follow the recommendations of prior family business research (Lane et al 2006) that suggest to guide Autonomy in family firms through explicit, written guidelines (Mazzola et al 2008). In addition, our findings indicate that adherence to family-related, often non-financial goals can lead to an unhealthy level of Risk-Taking.…”
Section: Resultsmentioning
confidence: 99%
“…Harris et al (1994) found little difference in family firms' strategic management processes with regard to internationalising, as compared with non-family firms. However, family firms which do use formal strategic planning appear to benefit developmentally (Mazzola/Marchisio/Astrachan 2008) and to internationalise more actively (Rienda et al 2005). 7 Ding et al (2008) also found that Chinese family firms performed significantly better than state-owned companies on five financial ratios between 1999 and 2004.…”
Section: Endnotesmentioning
confidence: 97%
“…In all cases the educational mode is important, where planning is used to teach managers/board members/family owners a systematic way to think about and work with strategy, and as a training practice for the next generation (Mazzola et al, 2008). In our cases, strategic planning definitely played such a role for the young owner-manager taking over BW after his father's sudden death.…”
Section: Discussionmentioning
confidence: 96%
“…A main theme in literature on strategic planning in family firms is that owner-family values and interests are incorporated into the planning (Carlock & Ward, 2001;Mazzola et al, 2008;Ward, 1988). This may have several implications.…”
Section: Family Firms As Context For the Strategic Practice Of Planningmentioning
confidence: 98%
See 1 more Smart Citation